Application of Design Thinking in creating environmentally friendly packaging designs for MSMEs in the food and beverage sector - Mohammad Fanani; Stivaniyanti Atmanegara; Elindawati Elindawati (International Journal of Multidisciplinary Sciences and Arts, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the food and beverage sector play a crucial role in the national economy and have shown rapid growth in the digital era (JDIH BPK RI, 2008; Indonesian SMEs, 2023). The widespread use of internet-based delivery services facilitates product distribution but simultaneously increases the consumption of single-use plastic packaging, which poses serious environmental challenges (Databoks, 2021; Waste-free, 2021). Plastic waste constitutes approximately 17% of total national waste (National Waste Management Information System, 2020), highlighting the urgency for innovative and sustainable solutions (Ministry of Environment and Forestry, 2021). This study aims to design environmentally friendly packaging for MSMEs in the food and beverage industry by integrating user needs with sustainability considerations. The research employs a design thinking-based innovation approach that includes stages of problem exploration, concept development, and product testing (Lewrick et al., 2020). The focus is on developing primary packaging solutions for soupy foods and cold beverages distributed through online delivery platforms. The findings reveal that eco-friendly packaging materials can effectively reduce reliance on single-use plastics while maintaining usability and convenience (Fischer et al., 2019). Moreover, the right packaging design not only promotes environmental sustainability but also enhances the competitiveness of MSMEs in the market (Louw & Kimber, 2007). In conclusion, implementing eco-friendly packaging innovations represents a strategic and effective approach to minimizing plastic waste impacts while ensuring the efficient and sustainable distribution of food and beverage products.